Potential of waste material as coarse aggregates for lightweight concrete production: A sustainable approach - Usmani, M. U.; Khairunisa, Muthusamy (Penerbit UMP, 2023)
In recent times, there has been growing interest in utilizing waste materials as coarse lightweight aggregates in the production of lightweight aggregate concrete. This approach has been gaining momentum as it has the potential to address the environmental concerns that come with conventional construction practices. The objective of this review paper is to evaluate the viability and potential of waste materials as coarse lightweight aggregates for producing lightweight aggregate concrete. This paper reviews the current research on various types of waste materials, including waste plastic, recycled concrete aggregate, slag, fly ash, and expanded polystyrene, as potential candidates for coarse lightweight aggregates. The paper highlights the properties and characteristics of these waste materials and their suitability for use as coarse lightweight aggregates. Additionally, the evaluation explores the mechanical characteristics of lightweight aggregate concrete that is generated using waste materials as coarse lightweight aggregates. Specifically, it compares the compressive strength, splitting tensile strength, flexural strength, and modulus of elasticity of lightweight aggregate concrete that includes waste materials with those of typical concrete. Furthermore, the paper discusses the sustainability benefits of using waste materials as coarse lightweight aggregates. By using waste materials in construction, not only are resources conserved, but waste is also diverted from landfills, reducing the negative impact on the environment. In conclusion, this review paper demonstrates that the use of waste material as coarse lightweight aggregate for lightweight aggregate concrete production is a viable and sustainable approach. The application of waste materials as coarse lightweight aggregates in lightweight aggregate concrete demonstrates mechanical characteristics that are similar to traditional concrete. Moreover, utilizing waste materials in this manner provides environmental advantages. This study offers valuable insights into the implementation of waste materials in construction, and it emphasizes the possibility of further exploration and advancement in this domain. For this review, a total of 15 articles were analyzed, with publication dates ranging from 2005 to 2021. The study contributes to several Sustainable Development Goals (SDG 9/11/12/13) set by the United Nations such as providing insights into the role of industry, innovation, infrastructure, sustainable cities, responsible consumption, production practices, and climate action.